Frequency and pattern of gynecological problems of adolescent girls attending outpatient department, department of obstetrics and gynecology, Bangabandhu Sheik Mujib Medical University, Bangladesh - Pervin, Hasna H.; Kazal, Rezaul K.; Parveen, Tabassum; Fatema, Kaniz; Chowdhury, Saima A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Adolescent is a stage of development tangent, like a bridge of childhood and adulthood. It is the healthiest age group of our society which is almost 20% of our total population. World health organization (WHO) defines adolescents are in the 10-19 year in age group. One of the major physiological changes that take place in adolescent girls is the onset of menarche, which is often associated with problems of irregular menstruation, excessive bleeding and dysmenorrhea. Methods: This cross-sectional observational study was carried out in 668 female adolescent aged 10-19 years irrespective of their marital status visiting the OPD of obstetrics and gynecology department of BSMMU. All data was analyzed using SPSS program version 22.0. Results: Results were expressed in frequencies or percentages. Of the 668 adolescent girls, 418 (62.6%) had different type of menstrual disorder. Of these 418 cases about 127 (30.38%) of them were a case of puberty menorrhagia, 109 (26.07%) cases were oligomenorrhoea and 91 (21.77%) were amenorrhea. Other presentations were pre-vaginal discharge, vulval itching, lower abdominal pain, dysuria, feeling lump in lower abdomen, mastalgia, feeling lump in the breast, discharge from breast, acne, hirsutism. Conclusions: This study shows more than half of adolescent girls are having menstrual disorder. Adolescent gynecology needs increased awareness and greater attention to improve the quality of their life. Setting up a separate adolescent clinic is necessary for efficient management of adolescent problem.